IMPLEMENTING OF VIRTUAL REALITY TECHNOLOGY IN SCIENCE SUBJECTS AS EFFORT TO BUILD A MEANINGFUL LEARNING - Aswie, Viqhi; Abdu, Wamaungo Juma (Tatar Pasundan: Jurnal Diklat Keagamaan, 2023)
The post-COVID-19 pandemic has resulted in learning loss in almost all subjects, including science learning. In addition, there is a decrease in motivation in capturing learning. In contrast, 21st-century education demands literacy skills accompanied by competencies and characters that lead to lifelong learning. Therefore, services in the form of technology that can improve students' skills and interests are needed, one of which is using virtual reality. This technology is believed to be a future asset that can help students construct their cognitive structures. Thus, this study aims to examine the use of virtual reality technology in improving meaningful learning in science learning at school. The method used in this study is a qualitative method with a descriptive approach through a literature review of Google Scholar and Scopus-indexed journals.Â  The data that has been collected is analyzed by correlating the relationship between the use of virtual reality with meaningful learning in science subjects. After that, it ends by elaborating on the ideas in this article. Based on studies that have been conducted, it is found that virtual reality is a 3D technology that helps visualize science concepts that combine the real and virtual worlds (immersive) so that learning is more interactive. Despite its great potential, this technology should be used as a supporting tool, not a substitute for human interaction in learning. Virtual reality can also create meaningful learning by directly involving students in constructing their cognitive structures related to facts, concepts, procedures, and metacognition. In addition, this technology is also able to integrate science concepts that were previously fragmented to be integrated comprehensively through 3D virtual simulations. This will help create meaningful learning because students can understand science concepts comprehensively by connecting their experiences to real learning materials through immersive technology.Â Keywords: Immerse Technology; Meaningful Learning; Science Subject; Virtual Reality